Personality and sensation seeking in high-risk sports - Klinar, P.; Burnik, S.; Kajtna, T. (Acta Gymnica, 2017)
Background: Personality represents a relatively consistent and unique sum of psychological, cognitive and physical characteristics of an individual. Sensation seeking is defined as an action, characterized by the search for different, new, complex and intensive emotions and experiences and preparedness to take physical, social, legal and financial risks in order to achieve these experiences.